Violence- A Shared Experience of Colored Women - Chapagaee, Rajendra Prasad (Journal of Development Review, 2022)
Violence reproduces the system of aggression and carries emotive states of individuals. Power and violence are interrelated. The definition of violence differs according to the definitions of power and politics. It gets disclosure according to its relation with their attachment with the social system and human relations. All forms of violence have short- and long-term negative effects on mental, physical and spiritual well-being. Ritual legitimizes the violence with the notion of death that is ever present in any sacrificial ritual. Women of color have to endure different types of violence. Psychological and spiritual violence cannot be seen and easily be measured for it is the matter of personal feeling and experience. Black women have to endure violence in their own home, their culture and general society. They find themselves suspended spiritually, culturally, economically and psychologically carrying the burden of multiple fold repression as black women. They are doubly repressed as being black in racial society and being women in patriarchal society. Racial, ritual and sexual violence, repression and resistance constitute black experience as a part and parcel of colored women of American life